Nano technology - Infused Azolla Manure: Improving Rice Stem Thickness in Sustainable Agriculture - M Ishwarya Niranjana; I Jeya Daisy; M D Saranya; K Gayathree; Chandramauli Awadhesh; Singh Raminder (E3S Web of Conferences)
Nano materials were integrated into the Azolla manure to enhance its nutrient delivery and promote a more efficient chemical reaction in the soil, improving plant growth. The experiment was conducted over a 2500 square feet area, with two groups: Group 1 utilizing nano-enhanced Azolla manure and Group 2 using traditional Goat manure. Each group contained 20 samples, for a total of 40 samples. The G-power calculation indicated a sample size with 85% power and a 90% confidence interval, and SPSS software was used for statistical analysis. Results revealed that the nano-enhanced Azolla manure significantly increased stem diameter, with a maximum recorded value of 4.3mm per plant after 120-145 days, compared to 3.4mm in the Goat manure group. This difference was statistically significant, with a p-value of 0.0026 (p < 0.05). The improved performance of the nano-enhanced Azolla manure is attributed to the optimized nutrient absorption and enhanced chemical interactions facilitated by the nano materials. These findings suggest that nano-enhanced Azolla manure could serve as a superior organic fertilizer, offering a sustainable alternative to traditional fertilizers like Goat manure, and holds considerable potential for improving the mechanical properties of rice crops, particularly stem growth, in agricultural applications.